Regional policy in the Central and East European countries prior to the eastward enlargement of the EU, with special focus on regional policy developments in East Germany - Gerhard Heimpold (European Regional Science Association (ERSA), 2001)
The contribution investigates the status and the problems of establishing regional policies in selected CEE countries %28Czech Republic, Estonia, Poland, Slovenia, Hungary%29 in the preliminary stages of accession to EU. According to the rules of the European structural funds the European financial means can only be used, if the CEE applicants have their own regional policy which must be compatible to the regulations of the EU structural funds. The European Commission still criticises in its progress reports a number of deficits with respect to the formation of the regional policies in the applicant countries. From the Commission's viewpoint the deficits are seen particularly within the administrative area. The contribution deals itself not only with the administrative aspects, but above all with the conceptional arrangements of the regional policies in the applicant countries. It is investigated, how the CEE countries handle the area designation, whether there exists a regional policy strategy and what kind of strategy (growth vs. equalisation) will be preferred and whether there have been designed policy instruments being suitable to implement the regional policy strategy and what types of instruments are designated to be used. The outlined questions have played an important role since the beginning of the 90's also in Germany, when the new German Länder were integrated into the German and European regional policy. Therefore the East German experiences of developing a regional policy which corresponds to the existing regional problems are also included into the contribution. The contribution is based on the analysis of literature and documents about the regional policy in CEE countries and in the new German Länder as well as of documents of the EU, in which the regional policy of CEE applicant countries is analysed and evaluated.
Keywords: 330